Integrated ANP and TOPSIS Method for Supplier Performance Assessment - Natalia, Christine; Surbakti, Ita Primsa; Oktavia, Chendrasari Wahyu (Jurnal Teknik Industri, 2020)
A supplier has become one of the main factors that influence the success of a company's supply chain activities. Supplier assessment is vital as suppliers have different performance. This study aims at assessing supplier performance using the integration of ANP and TOPSIS methods. Supplier performance assessment was based on supplier criteria indicators. Weighting criteria used ANP used to determine the most significant influence criteria of supplier performance.Furthermore,Â  TOPSIS was also employed to obtain supplier preference. Eight criteria and twenty-five sub-criteria were used for the supplier performance assessment.Â  The three highest sub-criteria were specification of quality, the flexibility of order changes, and production capacity. The priority results for suppliers were sorted from the highest to lowest ratio values.Â